فعالية التخطيط الاستراتيجي على الأداء المؤسسي من خلال اءدارة المعرفة والتدريب في سلطنة عمان دراسة تطبيةية على مكتب وزير الدولة ومحافظ ظفار - Musallam Ajaham Musalllam Alkathiri
This quantitative study aimed to determine the level of effectiveness of strategic planning on institutional performance through knowledge management and training as intermediate variables, in the office of the Minister of State and the Dhofar Governorate. So, the objectives of the study were: to diagnose the effectiveness of strategic planning on institutional performance, and to detect it through knowledge management and training. This study used the descriptive analytical approach, it adopted the theory of Human relationship by Mayo (1924). The size of the population study was (819) employees, and a stratified random sample consisting of (264) employees was chosen. The researcher designed a questionnaire consisting of (58) items, distributed on four axes: strategic planning, knowledge management, training, and institutional performance. To achieve the objectives of the study, a statistical package was used for structural equation modeling (SPSS 25 AMOS 23). The findings revealed that: a level between high and relatively average in (strategic planning, knowledge management, training and institutional performance), the findings also indicated the presence of a positive and statistically significant effect at the level of significance (0.05) for strategic planning on both knowledge management and training and on institutional performance. The value of the path parameter or standard estimates is equal to (0.40) and has a positive trend, in addition to a strong and indirect impact of strategic planning on institutional performance, through knowledge management and training as intermediate variables. This study has mainly contributed to building a model for the relationship between strategic planning (as an independent variable) and institutional performance (as a dependent variable), through the positive role of intermediate variables together (knowledge management and training). Finally, this study recommended adopting this proposed model for the employees of the office of the Minister of State and the Dhofar Governorate.